The $n$-Generalized Schützenberger-crossed product of monoids - Çetinalp, Esra Kırmızı (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 512.5We study the $n$-generalized Schützenberger-crossed product from the viewpoint of combinatorial group theory and define a new version of this product. For given monoids of this new product,  we obtain a representation of the $n$-generalized Schützenberger-crossed  product of arbitrary monoids.